Analysis of Teacher Difficulties in Implementing the Independent Curriculum at Pakulonan 01 Elementary School - Nur Asyifa, Syaqila; Oktrifianty, Erdhita; Magdalena, Ina (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
The Merdeka Curriculum is a structured and diverse classroom-based curriculum designed to be user-friendly for both teachers and students. In its implementation, the government grants schools full authority and responsibility to develop a curriculum that aligns with their specific needs and local cultures. However, due to insufficient training, teachers often feel unprepared to implement the Merdeka Curriculum effectively. This study aims to examine how the Merdeka Curriculum is enacted at SDN Pakulonan 01, South Tangerang City, identify the challenges faced by teachers during implementation, and explore potential solutions. This research employs a qualitative descriptive approach, collecting data through interviews, observations, and document analysis. The data was analysed using descriptive methods. Findings indicate that teachers encounter difficulties in three key areas: lesson planning, lesson delivery, and assessment. Challenges include adapting learning tools and methods for teaching modules, executing differentiated and project-based learning, limited infrastructure, and constraints in both formative and summative assessments. These findings offer recommendations for enhancing teacher training programmes and improving facilities.